Intraperitoneal insulin delivery provides superior glycaemic regulation to subcutaneous insulin delivery in model predictive control‐based fully‐automated artificial pancreas in patients with type 1 diabetes: a pilot study. Issue 12 (6th July 2017) - Dassau, Eyal; Renard, Eric; Place, Jérôme; Farret, Anne; Pelletier, Marie‐José; Lee, Justin; Huyett, Lauren M.; Chakrabarty, Ankush; Doyle, Francis J.; Zisser, Howard C.
Abstract : Aims: To compare intraperitoneal (IP) to subcutaneous (SC) insulin delivery in an artificial pancreas (AP). Research design and methods: Ten adults with type 1 diabetes participated in a non‐randomized, non‐blinded sequential AP study using the same SC glucose sensing and Zone Model Predictive Control (ZMPC) algorithm adjusted for insulin clearance. On first admission, subjects underwent closed‐loop control with SC delivery of a fast‐acting insulin analogue for 24 hours. Following implantation of a DiaPort IP insulin delivery system, the identical 24‐hour trial was performed with IP regular insulin delivery. The clinical protocol included 3 unannounced meals with 70, 40 and 70 g carbohydrate, respectively. Primary endpoint was time spent with blood glucose (BG) in the range of 80 to 140 mg/dL (4.4‐7.7 mmol/L). Results: Percent of time spent within the 80 to 140 mg/dL range was significantly higher for IP delivery than for SC delivery: 39.8 ± 7.6 vs 25.6 ± 13.1 ( P = .03). Mean BG (mg/dL) and percent of time spent within the broader 70 to 180 mg/dL range were also significantly better for IP insulin: 151.0 ± 11.0 vs 190.0 ± 31.0 ( P = .004) and 65.7 ± 9.2 vs 43.9 ± 14.7 ( P = .001), respectively. Superiority of glucose control with IP insulin came from the reduced time spent in hyperglycaemia (>180 mg/dL: 32.4 ± 8.9 vs 53.5 ± 17.4, P = .014; >250 mg/dL: 5.9 ± 5.6 vs 23.0 ± 11.3, P = .0004). Higher daily doses of insulin (IU) were delivered with the IP route (43.7 ± 0.1 vs 32.3 ± 0.1, P < .001) with no increased percent time spent <70 mg/dL (IP: 2.5 ± 2.9 vs SC: 4.1 ± 5.3, P = .42). Conclusions: Glycaemic regulation with fully‐automated AP delivering IP insulin was superior to that with SC insulin delivery. This pilot study provides proof‐of‐concept for an AP system combining a ZMPC algorithm with IP insulin delivery.